High Pressure Rheology of Lubricants (Part 4) - Masato Kaneko (Tribology Online)
The physical properties of lubricant under high temperature and high pressure include high pressure viscosity, high pressure density, bulk modulus, coefficient of thermal expansion, etc. It is important to know these high pressure physical properties in machine design. However, almost no discussion has been made on the liquid state equation, which is the basis of the high pressure physical properties of these lubricants. Therefore, in this report, using the high pressure density measuring device, the volume was obtained from the measurement of the density at each temperature and pressure, and the PVT relational equation was derived. Further, Vt=0 (absolute experiments, and it was found that this equation could be utilized as a liquid state equation of high utility. In addition, we can estimate the high pressure density which is one of the high pressure physical properties of the lubricant by this liquid state equation.